2023
DOI: 10.3390/genes14030590
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplastics Toxicity Specific to Liver in Inducing Metabolic Dysfunction—A Comprehensive Review

Abstract: Plastic pollution in the world is widespread and growing. The environment is swamped with nanoplastics (<100 nm), and the health consequences of these less visible pollutants are unknown. Furthermore, there is evidence that microplastics can release nanoplastics by digestive disintegration, implying that macroplastic exposure can cause direct and indirect disease via nanoplastics. The existence and impact of nanoplastics in numerous tissues from invertebrates to larger vertebrates that consume significant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 124 publications
(126 reference statements)
0
6
0
Order By: Relevance
“…Here, it was found that lipid accumulation is following a lysosomal stress response. In a mouse oocyte, BPA exposure is seen to cause lysosomal stress 114 . Nevertheless, lysosomal stress is not an isolated event in a cell.…”
Section: Mechanisms Of Bpa‐induced Nafldmentioning
confidence: 97%
See 3 more Smart Citations
“…Here, it was found that lipid accumulation is following a lysosomal stress response. In a mouse oocyte, BPA exposure is seen to cause lysosomal stress 114 . Nevertheless, lysosomal stress is not an isolated event in a cell.…”
Section: Mechanisms Of Bpa‐induced Nafldmentioning
confidence: 97%
“…113 NPs are known to alter gut-liver axis causing damage to liver and aggravating metabolic dysfunction. 114 Further, derangement of physiological gut-liver cross talk through dysbiosis can lead to NAFLD. 115 When PET microplastics (MPs) were combined with BPA, it was found that growth along with the toxic effects on liver was augmented in fish model.…”
Section: Nanoplasticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the toxicity of MPs conducted to date have shown that MPs exposure caused intestinal damage, liver infection, flora imbalance, lipid accumulation, and subsequently led to metabolic disorders [194]. Furthermore, MPs exposure increased the expression of inflammatory factors, inhibited acetylcholinesterase activity, reduced germ cell quality, and affected embryonic development [15,194].…”
Section: Perspectivesmentioning
confidence: 99%